THE CORRELATION BETWEEN WATCHING ENGLISH MOVIE HABIT AND VOCABULARY MASTERY IN THE NINTH GRADE STUDENT OF SMPN 9 DENPASAR IN ACADEMIC YEAR 2021/2022 - I Kadek Giri Artawan; Anak Agung Putu Arsana; Dewa Gede Agung Gana Kumara (Academic Journal on English Studies (AJOES), 2022)
This research was aimed to know: “There was significant correlation between students‟ habit in watching English movie and their vocabulary mastery SMPN 9 Denpasar in 2021/2022 academic year. The researcher methodology of this research was a quantitative. The population of the research was the ninth grade students of SMPN 9 Denpasar in 2021/2022 academic year, the number of students was 415 students. The sample of this research were 40 students. For collecting the data, researcher used two instruments which were questionnaire for students' habit in watching English movie and multiple choice test for vocabulary mastery. The result showed that there was significant correlation between students' habit in watching English movie and their vocabulary mastery in the ninth-grade of SMPN 9 Denpasar in academic year 2021/2022 with the correlation value was 0.633. It lied between 0.600-0.800 which was in a sufficient level.